Targeting Selectins and Their Ligands in Cancer - Natoni, Alessandro; Macauley, Matthew S.; O’Dwyer, Michael E. (Frontiers in Oncology, 2016)
Aberrant glycosylation is a hallmark of cancer cells with increased evidence pointing to a role in tumor progression. In particular, aberrant sialylation of glycoproteins and glycolipids have been linked to increased immune cell evasion, drug evasion, drug resistance, tumor invasiveness, and vascular dissemination leading to metastases. Hypersialylation of cancer cells is largely the result of overexpression of sialyltransferases. Humans differentially express twenty different sialyltransferases in a tissue-specific manner, each of which catalyze the attachment of sialic acids via different glycosidic linkages (2-3; 2-6 or 2-8) to the underlying glycan chain. One important mechanism whereby overexpression of sialyltransferases contributes to an enhanced metastatic phenotype is via the generation of selectin ligands. Selectin ligand function requires the expression of sialyl-Lewis X and its structural-isomer sialyl-Lewis A, which are synthesized by the combined action of alpha 1-3-fucosyltransferases, 2-3-sialyltransferases, 1-4-galactosyltranferases, and N-acetyl--glucosaminyltransferases. The α2-3-sialyltransferases ST3Gal4 and ST3Gal6 are critical to the generation of functional E- and P-selectin ligands and overexpression of these sialyltransferases have been linked to increased risk of metastatic disease in solid tumors and poor outcome in multiple myeloma. Thus, targeting selectins and their ligands as well as the enzymes involved in their generation, in particular sialyltransferases, could be beneficial to many cancer patients. Potential strategies include sialyltransferase inhibition and the use of selectin antagonists, such as glycomimetic drugs and antibodies. Here, we review ongoing efforts to optimize the potency and selectivity of sialyltransferase inhibitors, including the potential for targeted delivery approaches, as well as evaluate the potential utility of selectin inhibitors, which are now in early clinical development.